Joint photon statistics of photon-subtracted squeezed light - Coldenstrodt-Ronge, H; Smith, B; Puentes, G; Lundeen, J; Feito, A; Datta, A; Mosley, P; Eisert, J; Plenio, M; Walmsley, I (Optical Society of America, 2009)
We present the joint photon-number statistics of a locally photon-subtracted two-mode vacuum squeezed state of light. Comparison to the unsubtracted statistics shows a successful photon subtraction and the expected shift by one photon number. © 2008 Optical Society of America.